1996
DOI: 10.1097/00004647-199609000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral [15O]Water Clearance in Humans Determined by PET: I. Theory and Normal Values

Abstract: When used to measure blood flow in the brain, water leaves a residue in the vascular bed that influences the estimation of blood flow by current methods. To assess the magnitude of this influence, we developed a two-compartment model of blood flow with separate parameters for transport and vascular distribution of brain water. Maps of the water clearance, K1 into brain tissue, separated from the circulation by a measurably resistant blood-brain barrier (BBB), were generated by time-weighted integration. Depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
158
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(163 citation statements)
references
References 26 publications
5
158
0
Order By: Relevance
“…This significant reduction of parameters in the region of cerebral infarction was similar to a previous report (Temma et al, 2006). A single-compartment analysis used in the steady-state method may overestimate cerebral water clearance and tissue counts (Ohta et al, 1992(Ohta et al, , 1996; however, this method was established in human PET studies and many studies with CVD patients were reported (Yamauchi et al, 1996(Yamauchi et al, , 1998(Yamauchi et al, , 1999Okazawa et al, 2001;Ouchi et al, 2001). Although slightly different values were observed between the steady-state method and the bolus administration method in a previous study with CVD, the values were not significantly different (Okazawa et al, 2001).…”
Section: Discussionsupporting
confidence: 88%
“…This significant reduction of parameters in the region of cerebral infarction was similar to a previous report (Temma et al, 2006). A single-compartment analysis used in the steady-state method may overestimate cerebral water clearance and tissue counts (Ohta et al, 1992(Ohta et al, , 1996; however, this method was established in human PET studies and many studies with CVD patients were reported (Yamauchi et al, 1996(Yamauchi et al, , 1998(Yamauchi et al, , 1999Okazawa et al, 2001;Ouchi et al, 2001). Although slightly different values were observed between the steady-state method and the bolus administration method in a previous study with CVD, the values were not significantly different (Okazawa et al, 2001).…”
Section: Discussionsupporting
confidence: 88%
“…This effect, called ''signal enhancement by extravascular protons'' (SEEP) [Stroman et al, 2002c[Stroman et al, , 2003b[Stroman et al, , 2005b, is thought to arise from a local change in fluid balance, which in turn may result from changes in perfusion pressure, production of extracellular fluid, neurons and glial cells swelling, and maintenance of ion and neurotransmitter concentrations at sites of neuronal activity [Fujita et al, 1997;Ohta et al, 1996;Stroman and Andrew, 2007;Stroman et al, 2002cStroman et al, , 2003bStroman et al, , 2005b. Previous studies showed that both the BOLD and the SEEP effects give a contribution to the signal change observed during spinal fMRI activity, with different relative proportions depending on field strength and TE value used [Stroman, 2005;Stroman et al, 2002c].…”
Section: Discussionmentioning
confidence: 99%
“…According to this model, the radioactivity concentration in a brain region is expressed as follows (Iida et al, 1991;Ito et al, 2001;Ohta et al, 1996):…”
Section: Kinetic Analysismentioning
confidence: 99%